Fault detector on the sports walk. - Alvarado, C.; Villanueva, D. (Revista Mexicana de Ingenieria Biomedica, 1989)
One of the most frequent problems in walking tests is the appreciation of float faults. Except in obvious cases, these decisions are very controversial. Due to the above, sports medicine specialists who work with high performance athletes, found it interesting to have a device capable of monitoring these faults and thus establish training programs to minimize them. The proposed device visually and aurally indicates the flotation of the feet, in addition to keeping a count every time this occurs.